Impaired Cognitive Control of Emotional Conflict in Trait Anxiety: A Preliminary Study Based on Clinical and Non-Clinical Individuals - Yu, Yongju; Jiang, Chenggang; Xu, Haiyan; Yang, Qian; Li, Jiawen; Xu, Yuanyuan; Xiang, Wenjun; Peng, Li; Liu, Botao; Lv, Fang; Li, Min (Frontiers in Psychiatry, 2018)
Background: It has been observed that trait anxiety easily leads to conflict maladaptation under conflict circumstances. However, it remains unclear whether the precise neural mechanisms underlying the effects of high trait anxiety on cognitive control are consistent in high trait anxious individuals, with and without anxiety disorders. Methods: The present study recruited 29 healthy volunteers with low trait anxiety (LTA), 37 healthy volunteers with high trait anxiety (HTA), and 23 patients with generalized anxiety disorder (GAD). All participants completed demographic information, self-report measures of trait anxiety and depression. Then they performed the emotional flanker task with event-related potentials (ERPs) recorded. Results: Behavioral data manifested that, relative to LTA individuals, GAD patients displayed prolonged response times and increased error rates, while HTA individuals showed intact response times and accuracies. ERP data revealed that HTA individuals exhibited a trend towards more negative N2 amplitudes for conflict detection. In contrast, both HTA and GAD individuals displayed decreased P3 amplitudes for conflict resolution. ERP results indicated that both HTA and GAD individuals exhibited conflict maladaptation on the N2 amplitude. Correlation analyses also showed that the increased anxiety symptoms were associated with longer reaction times, more error rates, lower P3 amplitudes, and more perturbations in conflict adaptation on reaction times and N2 amplitudes. Conclusions: Our results demonstrated a severely impaired cognitive control in GAD patients while a moderately impaired cognitive control in HTA individuals. Trait anxiety can indeed serve as a predominant factor at the onset and in the maintenance of GAD. Therefore, the trait anxiety reducing strategies may provide significant therapeutic gains.